(untitled) (International Journal of Environmental Sciences, 2025)
Classrooms are high-risk environments for airborne infection transmission due to dense occupancy and prolonged exposure periods. In this study, we evaluate the effectiveness of three infection mitigation strategies using the Wells-Riley model to quantify the event reproduction number (R₀) as an indicator of infection risk. The strategies examined include: (1) air cleaners, (2) disposable masks, and (3) an integrated strategy employing personal exhaust ventilation with physical barriers together with ventilation. Results from the infection risk analysis demonstrate that while air cleaner is insufficient to control pathogen spread, strategies that incorporate additional measures significantly reduce R₀. In particular, integrated personal exhaust ventilation with physical barriers yield the lowest R₀ values, indicating superior infection control performance. These findings offer valuable insights for educational institutions seeking to implement effective, evidence-based infection mitigation measures in classroom settings.